Reduction of pro-tumorigenic activity of human prostate cancer-associated fibroblasts using Dlk1 or SCUBE1 - Brigid Orr; O. Cathal Grace; Pam Brown; Antony C. P. Riddick; Grant D. Stewart; Omar E. Franco; Simon W. Hayward; Axel A. Thomson (The Company of Biologists, 2013)
SUMMARY Human prostatic cancer-associated fibroblasts (CAFs) can elicit malignant changes in initiated but non-tumorigenic human prostate epithelium, demonstrating that they possess pro-tumorigenic properties. We set out to reduce the pro-tumorigenic activity of patient CAFs using the Dlk1 and SCUBE1 molecules that we had previously identified in prostate development. Our hypothesis was that mesenchymally expressed molecules might reduce CAF pro-tumorigenic activity, either directly or indirectly. We isolated primary prostatic CAFs and characterised their expression of CAF markers, expression of Notch2, Dlk1 and SCUBE1 transcripts, and confirmed their ability to stimulate BPH1 epithelial cell proliferation. Next, we expressed Dlk1 or SCUBE1 in CAFs and determined their effects upon tumorigenesis in vivo following recombination with BPH1 epithelia and xenografting in SCID mice. Tumour size was reduced by about 75% and BPH1 proliferation was reduced by about 50% after expression of Dlk1 or SCUBE1 in CAFs, and there was also a reduction in invasion of BPH1 epithelia into the host kidney. Inhibition of Notch signalling, using inhibitor XIX, led to a reduction in BPH1 cell proliferation in CAF-BPH1 co-cultures, whereas inhibition of Dlk1 in NIH3T3-conditioned media led to an increase in BPH1 growth. Our results suggest that pro-tumorigenic CAF activity can be reduced by the expression of developmental pathways.